Justice for PLHIV Workers: Islamic and National Legal Approaches to Protecting Labor Rights - Yoga Saputra; Andi Agung Mallongi; Mukhlisah Amin (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2025)
Discrimination against individuals living with HIV/AIDS (PLHIV) in the workplace constitutes a grave violation of the principles of justice and non-discrimination upheld by both national and Islamic legal systems. This study examines the legal protection of PLHIV’s labor rights from the perspectives of national law and Islamic jurisprudence, and evaluates the extent to which the principle of justice is reflected in employment practices across Indonesia. Employing a normative juridical approach, this research collected data from a literature review of national regulations, human rights principles, and the objectives of Islamic law (maqāṣid al-sharī‘ah). The findings reveal that despite the existence of legal protection, its implementation remains insufficient. Discrimination resulting in recruitment rejections, employment terminations, and restricted career advancement persists. These conditions have been exacerbated by societal stigma and weak legal enforcement. From the perspective of Islamic law, the imperatives of ḥifẓ al-nafs (protection of life) and ḥifẓ al-‘ird (protection of dignity) underscore the necessity of equitable treatment for all individuals. The study recommends an integrative approach that combines national and Islamic legal frameworks to ensure more comprehensive and just protection for PLHIV workers. Reinforcing regulatory mechanisms, eliminating HIV-negative certification requirements in hiring processes, and conducting widespread public education are essential steps toward fostering a more inclusive, stigma-free work environment.